INFLUENCE OF METOPROLOL SUCCINATE ON REGULATORY AND ADAPTIVE STATUS OF PATIENTS WITH CHRONIC HEART FAILURE FUNCTIONAL CLASS I. RESULTS OF NOT COMPARATIVE STUDY - V. G. Tregubov; S. G. Kanorskiy; V. M. Pokrovskiy (Рациональная фармакотерапия в кардиологии)
Aim. To estimate metoprolol succinate effect on regulatory and adaptive status (RAS) of patients with сhronic heart failure (CHF) functional class (FC) I and arterial hypertension (HT) I-II stages. Material and methods. 51 patients with CHF FC I and HT I-II stage, (30 men and 21 women aged 52.6±1.4 yeas). Cardio-respiratory synchronism (CRS) test, 6-minute walking test, tread-mill burden test with registration of maximal oxygen consumption, 24-hour blood pressure monitoring, echocardiography and determination of N-terminal pro-brain natriuretic peptide (NT-proBNP) blood level were performed initially and after 6 months of therapy with metoprolol succinate (dose 78.1±5.7 mg/day) in sustained-release presentation. Results. Metoprolol succinate therapy had no significant effect on RAS (there was no unidirectional dynamics of the basic CRS test parameters: a range of synchronization decreased significantly from 8.8±0.4 to 7.2±0.6 сardio-respiratory cycles per minute (in 18%; р<0.05), and duration of CRS development on the minimal boundary from 18.8±2.2 to 14.3±1.2 сardiocycles (in 24%; р<0,05); RAS index considerably did not change), myocardium structure, exercise tolerance and neuro-humoral activity. Metoprolol therapy only moderately improved left ventricle diastolic function. Conclusion. Metoprolol succinate therapy has no significant effect on RAS of patients with CHF FC I and HT I-II stages.